An Analysis Of The Reliability 150 kV High Voltage Air Line Conductors Towards Electric Field Strength - Muhammad Romim; Solly Aryza; Dicky Lesmana (Sean Institute, 2024)
Analysis of conductor reliability on 150 kV high voltage overhead lines (SUTT) against electric field strength is important to ensure the stability and safety of electricity distribution. This study aims to analyze the impact of electric field strength generated by 150 kV SUTT conductors on the operational reliability of the line, including its effect on system performance and the safety of the surrounding environment. Measurements and simulations of electric field strength were carried out at various distances from the conductor to understand the distribution of the electric field generated. The results of the study indicate that high electric fields around the conductor can affect the performance of the insulator, increase the risk of corona, and reduce the operational life of the line components. In addition, the electric field generated can also affect human health if exposure exceeds the limits recommended by safety standards. From the results of this analysis, it is recommended to routinely monitor the electric field strength around the line and implement mitigation measures to ensure long-term operational safety and reliability.